Energy and flux variations across thin auroral arcs - H. Dahlgren; B. Gustavsson; B. S. Lanchester; N. Ivchenko; U. Brändström; D. K. Whiter; T. Sergienko; I. Sandahl; G. Marklund (Annales Geophysicae, 2011)
Two discrete auroral arc filaments, with widths of less than 1 km, have been analysed using multi-station, multi-monochromatic optical observations from small and medium field-of-view imagers and the EISCAT radar. The energy and flux of the precipitating electrons, volume emission rates and local electric fields in the ionosphere have been determined at high temporal (up to 30 Hz) and spatial (down to tens of metres) resolution. A new time-dependent inversion model is used to derive energy spectra from EISCAT electron density profiles. The energy and flux are also derived independently from optical emissions combined with ion-chemistry modelling, and a good agreement is found. A robust method to obtain detailed 2-D maps of the average energy and number flux of small scale aurora is presented. The arcs are stretched in the north-south direction, and the lowest energies are found on the western, leading edges of the arcs. The large ionospheric electric fields (250 mV m −1 ) found from tristatic radar measurements are evidence of strong currents associated with the region close to the optical arcs. The different data sets indicate that the arcs appear on the boundaries between regions with different average energy of diffuse precipitation, caused by pitch-angle scattering. The two thin arcs on these boundaries are found to be related to an increase in number flux (and thus increased energy flux) without an increase in energy.